Contributions of the French administrative thought to public administrative science: From Jean Bodino to Charles-Jean Bonnin/Aportes del pensamiento administrativo francés a la Ciencia de la Administración Pública: Recorrido histórico (Encuentros, 2019)
This paper attempts to study the contributions of French thought for the science of public administration. It is an exploratory, historical study of documentary review. Results reveal: in the first place, Jean Bodin is considered the first theorist in the public administration field; secondly, we have the contributions made by Anne Robert Jacques Turgot, public administrator in service of the French absolutism, Alexis de Tocqueville, who focused his attention in State activity and Montesquieu, who spread in the West the system discovered by Aristotle: separation of powers. In a third moment, the administrative thought of the absolutism is described: cameral sciences and police science as the closest precedent to public administration science. Finally in a fourth moment, we have the contributions of Jean Charles Baptiste Bonnin, who published his Principles of Public Administration in the context of the French Revolution in the late XVII century. We conclude that the contributions of the French administrative thought constitutes the fundamental precedent in the development of the public administration science and we agree with Guerrero (1986a) who points out administration science is born in France in 1808 with Bonnin’s thought, which allows us to state that administration sciences is a scientific fieldKeywords: French administrative thought; public administration science; absolutist State; cameral sciences; police sciences; French Revolution.